Identity and Social Roles: a Relational Perspective - Bellini, Pier Paolo (Italian Sociological Review, 2016)
Starting from the hypothesis that identity is the result of interactions between the self and others, that it is, so to speak, their emergent effect, this article aims to identify the critical points of this bipolar relationship (ego-alter) that emerge in today's society. In particular, by focusing on the identity function of social roles, it emphasizes the complementary synergy needed in order to acquire them: recognition (by the individual with authority to do so) and acceptance (by the agent). In line with relational theory, we conclude that the reduction of personal identity to the more or less successful acquisition of social roles is likely to reduce the individual and his/her relationships to a simple instrumental function. We reaffirm, on the contrary, the need to restore a super-functional relationship between people that is able to preserve the social system and, at the same time, individual necessities.